The Psychology of Study Success in Universities, 1st edition - Kaarina, Maatta (Routledge, 2020)
Universities around the world are under increasing pressure to maintain high levels of graduation and to make study processes as efficient as possible, with teachers and students struggling to meet the expectations placed upon them as a result. The Psychology of Study Success in Universities asks whether it is possible to meet these demands at the same time as protecting the well-being of students. Drawing on an extensive and detailed analysis of study success in universities in Finland, the authors of this thought-provoking work argue that universities should be more concerned with students’ satisfaction and place greater weight on students’ perceptions of the elements that enhance or hinder their success.